2008
DOI: 10.1017/s1477200008002715
|View full text |Cite
|
Sign up to set email alerts
|

First record ofColeura(Chiroptera: Emballonuridae) on Madagascar and identification and diagnosis of members of the genus

Abstract: First record of Coleura (Chiroptera: Emballonuridae) on Madagascar and identification and diagnosis of members of the genus Abstract The genus Coleura contains two species: C. seychellensis restricted to the Seychelles Archipelago and C. afra broadly distributed on the African continent and the Arabian Peninsula. We recently captured and collected specimens of Coleura from Madagascar, an island from which it was previously unknown. Using museum specimens and the new material from Madagascar, we review morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Found in tropical and subtropical regions, 54 species of bats belonging to the family Emballonuridae are currently known (Simmons et al 2005;Goodman et al 2006Goodman et al , 2008Lim et al 2010). Among those, 17 are recognized in Brazil (Nogueira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Found in tropical and subtropical regions, 54 species of bats belonging to the family Emballonuridae are currently known (Simmons et al 2005;Goodman et al 2006Goodman et al , 2008Lim et al 2010). Among those, 17 are recognized in Brazil (Nogueira et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Coleura afra is the smallest species of the family in Africa and is distinguished from all other Emballonuridae by the absence of a gular sack and radio carpal pouches, a body weight of 10-12 g, its deep brown fur which is paler at the base than at the tip, its smaller size (Fore Arm < 55 mm) and the three pairs of lower incisors [1,9,10,28,33,34,35]. The bat generates sound through tongue clicks or vocalization that occurs as paired clicks and stretches into the ultrasonic range (20 kHz -100 kHz); essential in communication and navigation purposes [12,17,25].…”
Section: Introductionmentioning
confidence: 99%
“…The Ankarana bat species assemblage is also notable in including one of only two known occurrences in Madagascar of colonies of Coleura afra (Peters 1852) (Emballonuridae), which occurs in Africa as well (Goodman et al. , 2005; Goodman, Cardiff & Ratrimomanarivo, 2008a). Previous work at Ankarana suggested that hunting, which is illegal in the Reserve but legal most of the year outside of it, and roost site disturbance by tourists and artisanal miners were potential concerns for at least some of these species (Wilson et al.…”
Section: Introductionmentioning
confidence: 99%